Case Report: A Huge Calabash Heart: A Rare Case of Supracardiac Total Anomalous Pulmonary Venous Return - Tang, Jianjun; Wu, Zhihong; He, Jia; Hu, Qingdan; Yao, Jun; Hu, Lin; Zhou, Shenghua; Chen, Mingxian (Frontiers in Cardiovascular Medicine, 2022)
A 46-year-old woman was admitted to the cardiovascular department because of a 3-month history of palpitations and exertional dyspnea. She had a history of a successful pregnancy at a very young age. The chest radiograph presented a “calabash” configuration. Echocardiogram discovered a large atrial septal defect with a suspected pulmonary vein abnormality. Cardiac CT revealed supracardiac total anomalous pulmonary venous return, whereby, all the pulmonary veins drain into a vertical vein and, finally, to the superior vena cava. Cardiac catheterization was consistent with anomalous pulmonary venous drainage without pulmonary hypertension. Finally, she underwent a successful surgical repair and appeared asymptomatic before her discharge.